Comparison of treatment outcome between glucocorticoids and non-steroidal anti-inflammatory drugs in subacute thyroiditis patients—a systematic review and meta-analysis - Yuan, Anqi; Wu, Jialu; Huang, Hui (Frontiers in Endocrinology, 2024)
Importance: Subacute thyroiditis (SAT) is a self-limiting and inflammatory thyroid disease.Although SAT usually improves on its own within weeks, it needs treatment when patients have pain, fever, and symptoms of thyrotoxicosis. Therapeutic drugs mainly include non-steroidal antiinflammatory drugs (NSAIDs) and glucocorticoids. Currently, there is no systematic review orand meta-analysis of the comparison of outcomes between NSAIDs and glucocorticoids for the treatment ofto SAT.Objectives: To conduct a systematic review and meta-analysis on the outcomes in subacute thyroiditis patients treated with glucocorticoids or NSAIDs.